(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
A mycorrhizal fungus, Ceratobasidium sp. GC (NCBI Gene Bank Accession no GQ369961) associated with the roots of an epiphytic orchid Gastrochilus calceolaris was investigated by cultural morphology, microscopic features and molecular analysis of Internal Transcribed Spacer (ITS) regions sequences of nuclear ribosomal DNA. The colony appearance of the fungal endophyte was fluffy growth pattern and the colour of the young colony was milky white on both surfaces that turned in to brown at maturity on the upper surface and deep brown on reverse surface. The microscopic features of the fungus i.e. hyphal diameter, multi-nucleate vegetative cells, right angle branching pattern with slight constriction at branching point and a dolipore septum near the branching point were observed. All the characters corroborated the identity with anamorphic Rhizoctonia like fungi. The ITS regions sequences of nrDNA and phylogenetic analysis based on the neighbor-joining method showed clustered with Rhizoctonia like fungi, and the maximum identity (98.28%) with Ceratobasidium RR and Ceratobasidium FPUB isolated from Rhynchostylis retusa and Dactylorrhiza hetagera, respectively. Thus, the ITS of nrDNA sequences validated the morphological data. This is the first report of orchid mycorrhizal fungi from Bangladesh.